Listening Otherwise: Relationalities of the Othered - Campbell, Mark V. (Performance Matters)

(untitled) (Institute for Performance Studies, Simon Fraser University, 2023)
In this forum piece, I explore the potential of listening as a performative act by focusing on the experiences and skills essential to the practice of DJing. I find the field of remix studies a fruitful arena to expand and explore the possibilities of music studies beyond the silos of contemporary musical analysis and scholarship.